2019
DOI: 10.1101/823468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive fitness maps of Hsp90 show widespread environmental dependence

Abstract: Gene-environment interactions have long been theorized to influence molecular evolution. However, the environmental dependence of most mutations remains unknown. Using deep mutational scanning, we engineered budding yeast with all 44,604 single codon changes encoding 14,160 amino acid variants in Hsp90 and quantified growth effects under standard laboratory conditions and under five stress conditions (elevated temperature, nitrogen starvation, elevated salinity, high ethanol concentration, and oxidative stress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 80 publications
1
19
1
Order By: Relevance
“…Finally, we demonstrated that VIM-type variants have been continuously evolving by enhancing their resistance as well as altering their substrate specificity in nature. The study of natural variation also reinforces the observation that mutations found to be neutral or beneficial in an experimental setting tend to be enriched in nature as well 34,66 . It is likely that many new VIM variants will emerge in the future, and our results will provide a valuable basis to predict likely mutations and estimate the resistance of newly found variants.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, we demonstrated that VIM-type variants have been continuously evolving by enhancing their resistance as well as altering their substrate specificity in nature. The study of natural variation also reinforces the observation that mutations found to be neutral or beneficial in an experimental setting tend to be enriched in nature as well 34,66 . It is likely that many new VIM variants will emerge in the future, and our results will provide a valuable basis to predict likely mutations and estimate the resistance of newly found variants.…”
Section: Resultssupporting
confidence: 66%
“…Essential and temperature dependent residues display an enrichment of sidechain-backbone h-bonding relative to the proportion of h-bonding residues in each class ( Supplementary Fig. 8b, Supplementary Data 7), suggesting-when combined with the formation of a hydrophobic core-these residues are largely involved in protein folding and stability 39,46,66…”
Section: Elucidation Of the Role Of Residues In The Catalytic Domainmentioning
confidence: 99%
“…Moreover, like other molecular chaperones, HSP90 acts as a buffer upon environmental stress conditions by supporting folding and activation of client proteins. Accordingly, a recent study found that HSP90 has evolved to support growth in multiple stress conditions, and thus to provide cellular robustness [ 119 ].…”
Section: Protein Quality Controlmentioning
confidence: 99%
“…More recently, this work was expanded to encompass a large and complete multiallelic intragenic fitness landscape of 640 systematically engineered mutations in the protein. Intriguingly, they report local ruggedness in the fitness-landscape topography as well as the existence of epistatic hotspot mutations which combine to render predictability inherently difficult in the absence of mutation-specific information [223] . The study in Arabidopsis is even more epic.…”
Section: Alternative Functional Syntheses Of Evolutionary and Moleculmentioning
confidence: 99%